NEW DATA ON RUBIDIUM LEPIDOLITE - Skosyreva M.V.; Vlasova Ye.V. (My University, 1989)
During an exhaustive investigation of mica from rare-metal deposits, the authors made a detailed study of the rubidium variety of the lepidolite from East Siberian granitic pegmatite that has a lithium-cesium-tantalum complex mineralization. This mica consisted of large platy (3 cm × 5 cm) segregations of pinkish to lilac color and was confined to albitization zones, often near quartz nuclei, where it existed in association with cleavelandite, rubidium muscovite, tantalite and other rare-metal minerals. The investigation has identified a distinct relationship between the rubidium content of lepidolite and the fine structure of the IR spectrum, in particular the degree of splitting of the bands representing valence vibrations of the OH group, and they have found that it can be used as an important diagnostic indicator of rubidium lepidolite. These data have practical importance, because rubidium lepidolite is a typomorphic mineral of polymetallic rare-metal pegmatite deposits that are promising sources of rare elements.